Storytelling activities and comprehension of preschool children - Yap, Leonor G.; Tordecilla, Maria Jennifer (2002.)
Researchers have pointed out the significance of storytelling in the lives of young children as it has proven its worth through time. This study was aimed at identifying influences of storytelling activities to the comprehension preschool children.The participants a total of 34 children and 5 storytellers came from the two preschools in Quezon City, namely, University of the Philippines Child Development Center (UPCDC) and Early Years Academy (EYA). The exploratory nature of the research obtained 10 storytelling observations from these schools. Data was analyzed through an event sampling method and interviews with the children and the storytellers provided for the study's more accurate end result. From the data gathered and videotaped observations and interviews, the researcher was able to identify and discuss the frequency of storytelling activities that influenced child comprehension through the storyteller's discipline strategies, curriculum-related activities, and the use of gestures and voice props. Comprehension indicators such as the story structure and story-child experience link were also analyzed. More so, other factors that influences preschool comprehension also emerged. Alongside, two patters of adult-child interaction were observed in the study. The first was the one-way pattern where limited amounts of adult-child interaction were seen and second was the interactive or two-way pattern of storytelling where much use of storyteller scaffolding was reflected throughout the story's discussion. In general, the two-way pattern indicated high levels of child involvement in the story and signified a correlation with Vygotsky's theory of social collaboration between adult and child as an ideal. Other factors such as the developmental characteristics of children, storyteller ability, and the school's philosophy also influenced the comprehension of preschool children. In the light of the findings in the study, recommendations were considered as supplemental to future research.
Thesis (M. Family Life and Child Development)--University of the Philippines Diliman
Keywords: Storytelling -- Philippines; Reading comprehension